2006
DOI: 10.1074/jbc.m601239200
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylinositol 5-Kinase Stimulates Apical Biosynthetic Delivery via an Arp2/3-dependent Mechanism

Abstract: The mechanisms by which polarized epithelial cells target distinct carriers enriched in newly synthesized proteins to the apical or basolateral membrane remain largely unknown. Here we investigated the effect of phosphatidylinositol metabolism and modulation of the actin cytoskeleton, two regulatory mechanisms that have individually been suggested to function in biosynthetic traffic, on polarized traffic in Madin-Darby canine kidney cells. Overexpression of phosphatidylinositol 5-kinase (PI5K) increased actin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
44
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 68 publications
(63 reference statements)
5
44
1
Order By: Relevance
“…It might therefore be more accurate to think of PTEN function as simply preventing PtdIns(3,4,5)P 3 accumulation at the apical surface than as a major source of PtdIns(4,5)P 2 . Consistent with this idea is the observation that phosphatidylinositol 5-kinase (PI(5)-kinase), a kinase known to stimulate PtdIns(4,5)P 2 production, localized to the apical region of MDCK cells and increased biosynthetic delivery of apical proteins (Guerriero et al 2006). There are likely to be additional mechanisms to generate and amplify apical PtdIns(4,5)P 2 that await discovery.…”
Section: Phosphoinositides In Cell Architecturementioning
confidence: 88%
“…It might therefore be more accurate to think of PTEN function as simply preventing PtdIns(3,4,5)P 3 accumulation at the apical surface than as a major source of PtdIns(4,5)P 2 . Consistent with this idea is the observation that phosphatidylinositol 5-kinase (PI(5)-kinase), a kinase known to stimulate PtdIns(4,5)P 2 production, localized to the apical region of MDCK cells and increased biosynthetic delivery of apical proteins (Guerriero et al 2006). There are likely to be additional mechanisms to generate and amplify apical PtdIns(4,5)P 2 that await discovery.…”
Section: Phosphoinositides In Cell Architecturementioning
confidence: 88%
“…that stimulate formation of N-WASP-Arp2/3-dependent actin comets and slowed by inhibitors of comet formation (Guerriero et al, 2006) (Fig. 1, route 1).…”
Section: Rho Gtpases and Actin Dynamics In Apical Deliverymentioning
confidence: 92%
“…Studies in polarized epithelial cells (MDCK) have shown that the Rho GTPase cdc42, an actin cytoskeleton organizer found at the Golgi (Erickson et al, 1996;Kroschewski et al, 1999;Musch et al, 2001), actindepolymerizing drugs (Lazaro-Dieguez et al, 2007), and Arp 2/3 (Rozelle et al, 2000;Guerriero et al, 2006) affect differentially the exit of apical and basolateral proteins from the TGN. In none of these cases, however, the specific roles of This article was published online ahead of print in MBC in Press (http://www.molbiolcell.org/cgi/doi/10.1091/mbc.E08 -08 -0891) on November 5, 2008. the actin cytoskeleton in cargo protein exit have been documented.…”
Section: Introductionmentioning
confidence: 99%